COVER, EDITORIAL, FROM THE DESK OF THE EDITOR - Admin Jubir (UPN Veteran Yogyakarta, 2023)
Dear Readers,Yeay, we are entering our second year! Now we have an ISSN. We hope several month later we will get Sinta accreditation. We would like to thanks to all of the authors who publish their papers here. There are various topics issued in this edition, from nance (around financial literacy, financial satisfaction, financial behavior; and also size effect anomaly in Indonesia Stock Exchange); marketing (puchase decision associated with halal label, BPOM label, and price; and also intention to use mobile payment); and human resources (the most numerous topics, the theme includes employee motivation, communication, career development, employee performance, and cyberloafing). We will publish a new edition every April and October, so make sure you take part in it.Happy reading!Editorial Team.